Ten years of NO2 comparisons between ground-based SAOZ and satellite instruments (GOME, SCIAMACHY, OMI) - Ionov, Dmitry; Goutail, Florence; Pommereau, Jean-Pierre; Bazureau, Ariane; Kyro, Esko; Portafaix, Thierry; Held, Gerhard [UNESP]; Ericksen, Paul; Dorokhov, Valery (My University, 2006)
SAOZ (Systeme d'Analyse par Observations Zenithales) is a ground-based UV-Visible zenith-sky spectrometer installed between 1988 and 1995 at a number of NDSC stations at various latitudes on the globe. The instrument is providing ozone and NO2 vertical columns at sunrise and sunset using the Differential Optical Absorption Spectroscopy (DOAS) technique in the visible spectral range. The ERS-2 GOME Ozone Monitoring Experiment (GOME) in 1995 was the first satellite mission to provide a global picture of atmospheric NO 2 with reasonable spatial and temporal resolution. It was then followed by SCanning ImAging spectroMeter for Atmospheric ChartographY (SCIAMACHY) onboard ENVISAT in 2002, and Ozone Monitoring Instrument (OMI) onboard EOS-AURA in 2004, with a similar capacity to monitor total NO 2. All these instruments are nadir viewing mapping spectrometers, applying the DOAS technique in the visible for deriving the NO2 total column. Here we present the results of NO2 long-term comparisons between GOME and SAOZ for the whole period of GOME operation since 1995 at all latitudes - tropics, mid-latitudes and polar regions - in both hemispheres. Comparisons are also shown with the most recently available SCIAMACHY and OMI data in 2004-2005. Overall, the daytime satellite measurements (around noon) are found consistent with sunrise ground-based data, with an average smaller difference at the tropics and mid-latitudes than in the polar areas in the summer. The agreement is even improved after correcting for the NO2 photochemical change between sunrise and the satellite overpass using a box model. However, some seasonal dependence of the difference between ground-based and satellite total NO2 still remains, related to the accuracy of photochemical simulations and the set of NO2 air mass factors used in the retrievals of both systems.
Keywords: Absorption spectroscopy; Imaging techniques; Nitrogen oxides; Ozone; Satellite communication systems; Ultraviolet devices; Differential Optical Absorption Spectroscopy (DOAS); GOME Ozone Monitoring Experiment (GOME); UV-Visible zenith sky spectrometers; Atmospheric chemistry